Risk factors for early mortality of lung cancer patients in France: A nationwide analysis. (14th May 2022) - Goussault, Hélène; Gendarme, Sébastien; Assié, Jean‐Baptiste; Jung, Camille; Epaud, Salomé; Algans, Christelle; Salaun‐Penquer, Noémie; Rousseau, Mathilde; Lazatti, Andrea; Chouaïd, Christos
Abstract: Background: Despite therapeutic advances, lung cancer remains the first cause of death from cancer. The main objective of this study was to identify risk factors associated with death within 3‐months of the first hospitalization for lung cancer in France. Methods: This analysis included patients with a first hospitalization for lung cancer (between January 1, 2016 and December 31, 2018) according to diagnosis‐related groups entered into the French national medical‐administrative database. Clinical and socioeconomic parameters and characteristics of that first hospitalization were analyzed. A model predictive of early mortality was developed based on those variables. Results: The 144, 087 included patients were 67% men; median age of 68 [interquartile range 60–76] years; 47% had metastatic disease at diagnosis; and 34% and 23%, respectively, had received systemic treatment or undergone curative surgery. The 3‐month mortality was 19%, and significantly higher for those ≥70 versus <70 years old (OR 1.33, 1.22–1.45), men versus. women (OR 1.50, 1.44–1.55), those with metastatic disease at diagnosis (OR, 3.30, 3.18–3.43), first hospitalization via the emergency room (OR 1.65 1.59–1.71) and first hospitalization lasting >30 days (OR, 1.58 1.49–1.68). In contrast, no socioeconomic characteristic was associated with early mortality. Conclusion: Almost 1 in 5 patients diagnosed with lung cancer in France died within 3 months post‐diagnosis. Improving survival requires diagnosis at an earlier stage and better organization of diagnosis and specific care pathways. Abstract : In France, almost 1 in 5 patients diagnosed with lung cancer died within 3 months following first hospitalization. Early mortality is higher for patients 70 years, for men, for those with metastatic disease at diagnosis, for patients hospitalized via the emergency room and with first hospitalization lasting >30 days.